2017
DOI: 10.1080/03630242.2017.1353575
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of lavender and bitter orange on sleep quality in postmenopausal women: A triple-blind, randomized, controlled clinical trial

Abstract: This trial compared the effects of lavender and bitter orange on sleep quality in postmenopausal women. This trial was conducted in 2015. Eligible postmenopausal women were allocated into one of two intervention groups or a control group (n = 52 per group) in a 1:1:1 ratio using a randomized block design. Intervention groups received 500 mg capsules containing only bitter orange or lavender flower powder, and the control group received 500 mg capsules containing starch. The Pittsburgh Sleep Quality Inventory w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
0
21
0
5
Order By: Relevance
“…In second trial, Kamalifard et al [16]. in duplicate publication published in Persian databases randomized 104 patients to two groups to receive 500-mg lavender capsule (n = 52) or 500-mg placebo capsule (n = 52).…”
Section: Resultsmentioning
confidence: 99%
“…In second trial, Kamalifard et al [16]. in duplicate publication published in Persian databases randomized 104 patients to two groups to receive 500-mg lavender capsule (n = 52) or 500-mg placebo capsule (n = 52).…”
Section: Resultsmentioning
confidence: 99%
“…One trial 15 compared 3 groups of bitter orange, lavender and placebo. The mean difference of Pittsburgh Sleep Quality Index (PSQI) total score showed more prominent decrease in the lavender group (MD = −0.596; P = 0.003; 95% CI, −0.989 to −0.203; P = 0.003; 1 trial) and bitter orange (MD = −0.665; P = 0.001; 95% CI, −1.059 to −0.270; 1 trial) compared to placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a great interest in these EOs has been observed in the context of alternative medicines such as aromatherapy. It was demonstrated that these substances, after vaporization and inhalation, are effective for treating different forms of anxiety, sleep, and libido, and reduce seizures in animal models [ 38 , 39 , 198 , 199 , 200 , 201 ]. The mechanism of action of the plant’s ingredients, however, is not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of the plant’s ingredients, however, is not fully elucidated. Anxiolytic and hypnotic effects are seemingly due to the combination of the action of the plant’s aroma on the limbic system through olfaction and the direct action of terpenes on GABAergic and serotoninergic (5-HT 1A ) receptors [ 39 , 202 , 203 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation